FRI0071 Responses to infliximab therapy in the attract trial assess with the disease activity score (das): clinical response measured by das at 102 weeks correlates with arrest of radiologic progression and shows higher response rate than acr20 criteria. (1st June 2001) - Antoni, CE; Kavanaugh, A; Manger, B; Keenan, G; Schaible, T; Harriman, G; Patel, K; Kalden, J
Abstract : Background: In the ATTRACT trial, the anti-TNF-monoclonal antibody infliximab showed significant improvement in disease activity score (DAS), reduction in signs and symptoms, inhibition of progression of structural damage and improved quality of life in rheumatoid arthritis (RA) patients, at 54 weeks. Inhibition of radiologic progression by infliximab occurred in both ACR20 responders and non-responders. This suggests that the ACR20 criteria might underestimate clinical responses to therapeutic agents. Objectives: To examine effect of infliximab on DAS RA patients after two years of treatment. Methods: DAS was calculated as follows: 0.56*SQRT(TJC) + 0.28*SQRT(SJC) +0.7ln (ESR) + 0.014*(pt global (VAS)). DAS responses were characterised as ?None?, ?Moderate? or ?Good? using DAS scores at 102 week and change in DAS from baseline to 102 week. Patients with ?Good? or ?Moderate? response were considered DAS responders. Fisher?s exact test was used to compare proportion of patients with DAS response by treatment group. Results: Clinical responses as measured by ACR20 and DAS correlated with each other; however, overall the response rate was higher with the DAS. At week 102, 84% of patients achieving ACR20 response were also responders using DAS; 45% of ACR20 non-responders were DAS responders. The DAS showed a statistically significant difference for each infliximab treatment group vs placebo (p < 0.001). ACR20 and DAS response rate at Wk 102 are presented below, by treatment group. Conclusion: Responses assessed with ACR20 and DAS have previously been shown to correlate. Analysis of data from the ATTRACT trial suggests that the DAS may be more sensitive to clinical improvement. The improved sensitivity of DAS, and the fact that it evaluates both change in response to therapy and also extent of residual disease activity, support its routine use as an endpoint in clinical trials.